Endogenous pneumoconiosis: Analytical scanning electron microscopic analysis of a case. (3rd May 2016) - Galeotti, Jonathan; Sporn, Thomas A.; Ingram, Peter; Wahidi, Momen M.; Roggli, Victor L.
ABSTRACT: Pneumoconiosis is often considered a disease of the lung initiated by exposure to dust or other airborne particles, resulting in injury to the lungs. The term "endogenous pneumoconiosis" has been used in the literature to describe the deposition of compounds on the elastic fibers of the lung, usually in the setting of cardiac failure. In the case we present here, the patient aspirated a foreign body resulting in damage to the lung tissue and subsequent deposition of endogenous compounds on the elastic fibers of the pulmonary parenchyma and vasculature. We determined the composition of this mineral and mapped the distribution of elements using a combination of backscattered electron microscopy and energy dispersive spectrometry.